Green transformations in Vietnam's energy sector. Issue 3 (9th August 2018) - Urban, Frauke; Siciliano, Giuseppina; Wallbott, Linda; Lederer, Markus; Dang Nguyen, Anh
Abstract: Vietnam has experienced rapid economic growth over the past few decades, as well as growing environmental pressures. The country is therefore pursuing strategies for green transformations, which are the processes of restructuring to bring economies and societies within the planetary boundaries. This article addresses the opportunities, barriers, and trade‐offs for green transformations in Vietnam's energy sector and examines them from an energy justice perspective. The article draws on in‐depths expert interviews with representatives from government agencies, private firms, academic institutions, and multilateral institutions in Vietnam. The article finds that Vietnam is undergoing efforts to move away from business as usual by promoting renewable energy and energy efficiency, as well as aligning energy and climate plans with national development priorities such as energy security and economic growth. Yet there is a need for more coordinated, integrated approaches and policies that span across the 3 areas that address green transformations in Vietnam: green growth, sustainable development, and climate change. Finally, although key actors seem to be aware and may be critical of major trade‐offs such as land grabs for energy projects, the impacts on affected people need to be better understood and mitigated.